Status of High Body Weight Among Nurse-Family Partnership Children. Issue 6 (November 2017) - Thorland, William; Currie, Dustin; Colangelo, Claire
Abstract: Purpose: Increased prevalence of high levels of body weight in early childhood has become a public health concern, given its potential association with adult obesity and related comorbidities. Both socioeconomic status and race-ethnicity are related to increased prevalence. The purpose of this study was to identify additional risk factors common to children of low-income families; and to guide quality improvement initiatives within home visiting programs, potentially fostering more desirable physical development outcomes. Study Design and Methods: A cohort of children ( n = 14, 318) of all mothers enrolled in Nurse–Family Partnership between 2007 and 2010 was evaluated. Measures consisted of demographics, health behaviors, and physical growth metrics collected by specially educated nurses during the course of home visits that also delivered the program model. Measures of weight (W) versus length (L) were converted to percentiles using the Centers for Disease Control and Prevention–World Health Organization norms with high W/L (≥97.7th percentile) defining a binary outcome. Multiple logistic regression modeling was then used to derive risk models for that outcome. Results: Across each of the four time points for body measures (child's age 6, 12, 18, and 24 months), race-ethnicity, prepregnancy body mass index (BMI), maternal weight gain, and breastfeeding duration emerged as common risk factors. Clinical Implications: Moderation of weight gain during pregnancy, extending breastfeeding duration, and normalization of BMI before subsequent pregnancies may potentially serve as means of lowering the prevalence of high body weight levels in young children of low-income families served by home visitors. Abstract : Obesity rates and their potential associations were evaluated in cohort of over 14, 000 children of mothers enrolled in the Nurse-Family Partnership, a program that includes nurse home visits. Results suggest moderation of weight gain during pregnancy, extending breastfeeding duration, and normalization of maternal body mass index before subsequent pregnancies may potentially be effective in lowering the prevalence of high body weight levels in young children of low income families.